Long-term repeated rituximab treatment for childhood steroid-dependent nephrotic syndrome - Ji Hyun Kim; Eujin Park; Hye Sun Hyun; Myung Hyun Cho; Yo Han Ahn; Hyun Jin Choi; Hee Gyung Kang; Il-Soo Ha; Hae Il Cheong (The Korean Society of Nephrology, 2017)
Background: Rituximab (RTX) can be used as a rescue therapy for steroid-dependent nephrotic syndrome (SDNS). However, the efficacy and safety of long-term, repeated use of RTX are not established. This study was conducted to assess the efficacy and safety of long-term, repeated RTX treatment in children. Methods: Eighteen consecutive child patients with SDNS who were treated with three or more cycles of RTX for one year or longer were recruited, and their medical records were retrospectively reviewed. Results: The patients were followed for 4.7 ± 1.9 years and received 5.2 ± 2.3 cycles of RTX over 2.8 ± 1.1 years. Approximately 70% of the additional RTX cycles were administered due to recovery of B-cells without relapse. The relapse rate decreased from 3.4 ± 2.0 per year initially to 0.4 ± 0.8 per year at the third year after RTX treatment. Approximately 10% of the RTX infusions were accompanied by mild infusion reactions. Eight patients showed sustained remission without any oral medication after the last cycle of RTX, while 10 patients had one or more episodes of relapse after the last cycle of RTX. The relapse rate in the latter group decreased from 2.8 ± 1.5 per year before RTX treatment to 1.3 ± 0.8 per year after cessation of RTX treatment. No significant differences in clinical parameters were found between the two groups. Conclusion: This retrospective study showed that pre-emptive and long-term, repeated RTX treatment is relatively effective and safe in children with SDNS. However, well-designed prospective studies are needed to confirm these findings.